POTTERIES OF PUEMAPE: A PETROGRAPHIC ANALYSIS OF CERAMICS FORMATIVE IN THE NORTHERN COAST OF PERU - Druc, Isabelle C. (2014)
This article presents the petrographic study of 21 thin sections of ceramics from the Formative site of Puémape, on the northern litoral of Peru, a site with strong afiliation to the Cupisnique culture. The results suggest the existence of several local productions, with a difference in resource area and manufacture between the Middle and Late Puemape phases. A graphite-on-red decorated bottle stands out as non local, for its intrusive composition and unique stylistic character. Its occurence is examined in view of other ceramics of similar type and composition found in the Jequetepeque valley.